Pancasila Education Teachers’ Perspectives on Deep Learning in the Context of Collaboration Dimension - Ervina Rizqiani; Novia Wahyu Wardhani (Universitas Negeri Semarang, 2026)
Deep learning in the context of collaboration has been implemented in grade ten at SMA Negeri 12 Semarang, specifically in the Pancasila education subject. However, its implementation has not been evenly distributed, as indicated by the presence of passive students and their limited contributions in group work. Encourage the necessity of an in-depth understanding of the teachers’ perspective as learning implementers. This study aims to explore the perspective of Pancasila education teachers on deep learning in the collaboration dimension and the teachers' endeavors to overcome these challenges. Using a qualitative approach with a case study design, the data were collected through observation, interviews, and documentation. The results of the study indicate that teachers perceive deep learning as an instructional approach that connects learning materials through collaborative activities. Teachers implement strategies such as role distribution, group management, and monitoring of collaborative processes to encourage student participation. The implementation of this learning approach must be supported by the availability of learning facilities and teacher training provided by the school. These findings highlight that the perspectives of Pancasila education teachers play a crucial role in optimizing deep learning within the collaboration dimension at SMA Negeri 12 Semarang.